Combined treatment with Sigma1R and A2AR agonists fails to inhibit cocaine self-administration despite causing strong antagonistic accumbal A2AR-D2R complex interactions: the potential role of astrocytes - Borroto-Escuela, Dasiel O.; Lopez-Salas, Alexander; Wydra, Karolina; Bartolini, Marco; Zhou, Zilong; Frankowska, Malgorzata; Suder, Agata; Benitez-Porres, Javier; Romero-Fernandez, Wilber; Filip, Malgorzata; Fuxe, Kjell (Frontiers in Molecular Neuroscience, 2023)
Previous studies have indicated that acute treatment with the monoamine stabilizer OSU-6162 (5 mg/kg), which has a high affinity for Sigma1R, significantly increased the density of accumbal shell D2R-Sigma1R and A2AR-D2R heteroreceptor complexes following cocaine self-administration. Ex vivo studies using the A2AR agonist CGS21680 also suggested the existence of enhanced antagonistic accumbal A2AR-D2R allosteric interactions after treatment with OSU-6162 during cocaine self-administration. However, a 3-day treatment with OSU-6162 (5 mg/kg) failed to alter the behavioral effects of cocaine self-administration. To test these results and the relevance of OSU-6162 (2.5 mg/kg) and/or A2AR (0.05 mg/kg) agonist interactions, we administered low doses of receptor agonists during cocaine self-administration and assessed their neurochemical and behavioral effects. No effects were observed on cocaine self-administration; however, marked and highly significant increases using the proximity ligation assay (PLA) were induced by the co-treatment on the density of the A2AR-D2R heterocomplexes in the nucleus accumbens shell. Significant decreases in the affinity of the D2R high- and low-affinity agonist binding sites were also observed. Thus, in low doses, the highly significant neurochemical effects observed upon cotreatment with an A2AR agonist and a Sigma1R ligand on the A2AR-D2R heterocomplexes and their enhancement of allosteric inhibition of D2R high-affinity binding are not linked to the modulation of cocaine self-administration. The explanation may be related to an increased release of ATP and adenosine from astrocytes in the nucleus accumbens shell in cocaine self-administration. This can lead to increased activation of the A1R protomer in a putative A1R-A2AR-D2R complex that modulates glutamate release in the presynaptic glutamate synapse. We hypothesized that the integration of changes in presynaptic glutamate release and postjunctional heteroreceptor complex signaling, where D2R plays a key role, result in no changes in the firing of the GABA anti-reward neurons, resulting in no reduction in cocaine self-administration in the present experiments.